SEXUAL SEPARATION AND GROWTH RATE IN GHUNGROO PIG (Indian Journal of Animal Production and Management, 2014)
The study was conducted at NRC on Pig (ICAR), Guwahati, Assam to standardize the best age to separate male and female piglets of recently registered Ghungroo pigs for optimizing production performance. Forty Six Ghungroo Piglets of 0.90±0.01 Kg birth weight were selected for the study. Three different treatments of differential age of separation of male and female were done, viz., under control, twelve males and females were separated at an age of 2 months; under T1, Forteen males and females were separated at an age of 3 months; and under T2, twenty males and females were separated at an age of 4 months. Significantly (p
Keywords: Ghungroo; Sexual Separation; Pig; Growth Rate